Pemetaan Sistem Informasi Geografis Jumlah Kelurahan Yang Mengalami Bencana Menurut Kecamatan Di Kota Bogor - Bima, Bima Aditya Hendriansyah; Bambang Agus Herlambang; Ahmad Khoirul Anam (JURNAL ILMIAH RESEARCH STUDENT, 2024)
The city of Bogor, located in an area that is vulnerable to various natural disasters, often faces serious challenges such as floods, landslides and fires. Flooding is mainly triggered by high rainfall and the city's contoured topography, resulting in waterlogging in several areas. Landslides, caused by the steep mountain slopes around Bogor, are a constant threat, damaging settlements and the city's infrastructure. Fires, whether caused by natural factors or human negligence, threaten the safety of citizens and cities. These disasters had a significant impact on the daily lives of Bogor residents, causing material losses, destroying infrastructure and harming the local economy. Therefore, serious efforts are needed in disaster mitigation planning, including early warning systems, development of disaster-resistant infrastructure, and public awareness to increase preparedness in facing the threat of disasters that often arise in this city. Collaborative efforts between the government, research institutions and the community are key in creating a safer and more sustainable environment in the city of Bogor